Impact of the “carbon trade—carbon tax” policy package on China’s macroeconomics and carbon emission reduction - Fei, Yanying; Jia, Cao (Frontiers in Environmental Science, 2024)
Introduction By constructing a computable general equilibrium model of "carbon trading" and "carbon trade-carbon tax", this study aims to deeply explore the combined impact of these two policies on China's economic development and carbon emission reduction, so as to provide scientific decision support for policy makers. Methods In order to accurately simulate the economic effects of carbon trading policies, the carbon trading module was introduced in detail in the "carbon trading" model, and the carbon trading cost was incorporated into the elastic substitution function production module. At the same time, in order to comprehensively evaluate the effect of the combination policy of "carbon trade-carbon tax", the cost of carbon tax is included in the constant elastic substitution function of production in the model. Results and Discussion Through in-depth data analysis and model calculation, it is found that although a single carbon trading policy can effectively promote the reduction of carbon emissions, its impact on the economy is relatively moderate, especially in promoting the technological upgrading of the power industry. The "carbon trade-carbon tax" combination policy has further strengthened the emission reduction action, in a number of industrial sectors, such as coal, power, heavy industry and light industry, by significantly increasing the cost of carbon emissions to promote emission reduction. The above results show that carbon tax policies play an important role in balancing carbon emission reduction and economic development. Compared with the single carbon trading policy, the introduction of carbon tax makes the emission reduction efforts of various departments more comprehensive, and also contributes to the stable development of the economy.